Advanced primary vaginal squamous cell carcinoma: A case report and literature review - Shen, Yue; Meng, Xiangkai; Wang, Lili; Wang, Xiaoxiao; Chang, Hua (Frontiers in Immunology, 2022)
Background Vaginal carcinoma is a gynecological malignancy with low incidence, and there are few relevant and specific guidelines for vaginal cancer in our country and abroad. Here, we report the case who was diagnosed with advanced, primary vaginal squamous cell carcinoma and underwent integrated treatment successfully. Case introduction A 64-year-old Chinese woman underwent subtotal hysterectomy for uterine fibroids in 1998 and laparoscopic extensive residual cervical resection, bilateral ovarian salpingectomy, and pelvic lymph node dissection for residual cervical adenocarcinoma (stage IB1) in the First Affiliated Hospital of China Medical University in 2018. There was no postoperative review. The patient experienced vaginal discharge in March 2020, and vaginal bleeding occurred in July 2020. Our patient was diagnosed with stage IVA vaginal squamous cell carcinoma, based on a gynecological examination, colposcopy biopsy with histopathological examination, computed tomography scan, and tumor marker levels by two professors. After three phases of treatment (sequential treatment with chemotherapy plus radiotherapy, chemotherapy combined with immune checkpoint inhibitors, and immune checkpoint inhibitors combined with tyrosine kinase inhibitors therapy), her condition improved. Her current state is generally good, and she has achieved complete remission. Conclusion We report a rare case of a patient with primary advanced vaginal carcinoma combined with cervical adenocarcinoma. The patient was treated for approximately 2 years, and her personalized treatment showed promising results. We will continue to follow up with the patient and monitor her response to the current treatment process.